RANCANG BANGUN APLIKASI DIGITAL STYLING BOOK MENGGUNAKAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID - Swandy Ciptakusumo Wisang; Hamdan Arfandy; Junaedy (STMIK KHARISMA Makassar, 2018)
The aim of the research is to build an interactive application which is able to be a helping instrument in deciding hair style and fashion style. In the process of creating this application, author used ActionScript 3.0 as programming language which supports powerful animation interface because Adobe Flash is used in creating animation. Testing methods used by author is a black box testing. The result can be stated that the system has been created by author goes according to plan and specification requirements system. Based on the result of the research, we can concluded that author has built interactive multimedia based application with Flash which is able to be a helping instrument in deciding hair style and fashion style.